2022
DOI: 10.1136/jitc-2022-005632
|View full text |Cite
|
Sign up to set email alerts
|

Metformin increases natural killer cell functions in head and neck squamous cell carcinoma through CXCL1 inhibition

Abstract: BackgroundMetformin slows tumor growth and progression in vitro, and in combination with chemoradiotherapy, resulted in high overall survival in patients with head and neck cancer squamous cell carcinoma (HNSCC) in our phase 1 clinical trial (NCT02325401). Metformin is also postulated to activate an antitumor immune response. Here, we investigate immunologic effects of metformin on natural killer (NK) and natural killer T cells, including results from two phase I open-label studies in patients with HNSCC treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Metformin treatment also increased natural killer cell infiltration and cytotoxicity in head and neck squamous cell carcinoma in patients by promoting perforin release secondary to an AMPK-independent and mTORC1–STAT1-mediated downregulation of CXCL1 (ref. 183 ) (Fig. 2b ).…”
Section: Metformin and The Immune Systemmentioning
confidence: 95%
“…Metformin treatment also increased natural killer cell infiltration and cytotoxicity in head and neck squamous cell carcinoma in patients by promoting perforin release secondary to an AMPK-independent and mTORC1–STAT1-mediated downregulation of CXCL1 (ref. 183 ) (Fig. 2b ).…”
Section: Metformin and The Immune Systemmentioning
confidence: 95%
“…Metformin shows anticancer activities in various malignancies, including colorectal cancer, thyroid cancer along with head and neck cancer. [31][32][33] A study has also revealed that type II diabetes patients who received metformin treatment have an obviously lower risk of MM. 34 Chidamide is a new oral benzamide-type selective HDAC inhibitor with anticancer activity in multiple cancers, such as hematologic cancer, lung carcinoma, and laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin shows anticancer activities in various malignancies, including colorectal cancer, thyroid cancer along with head and neck cancer 31–33 . A study has also revealed that type II diabetes patients who received metformin treatment have an obviously lower risk of MM 34 .…”
Section: Discussionmentioning
confidence: 99%
“…has shown that the antidiabetic agent metformin slows tumor growth and progression in vitro and in combination with chemoradiotherapy in patients suffering from head and neck cancer squamous cell carcinoma (HNSCC) in their phase 1 clinical trial (NCT02325401). It increases the activated peripheral NK cell populations, enhanced HNSCC NK cell cytotoxicity, and inhibited the CXCL1 pathway while stimulating the STAT1 pathway [ 52 ]. It also influences anticancer immunity in esophageal squamous cell carcinoma (ESCC) in both humans and mice, via triggering an AMPK activation and STAT3 inactivation.…”
Section: Immune Cells With Specific Phenotypes In Tmementioning
confidence: 99%